PEMANFAATAN GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF DI TENGAH DAMPAK PENYAKIT VIRUS CORONA 19 BAGI PENGAJAR - Fauzan, Fauzan Asrin (JURNAL BORNEO AKCAYA, 2020)
ABSTRACT The Corona Virus Diseas 19 (COVID 19) pandemic has become a global health problem today. Almost the whole world feels the effects of this deadly disease, either in the economic, governmental, and educational sectors. The Republic of Indonesia has endeavored to invite all educational institutions starting from the elementary schools to the tertiary education to study at home. It is deemed the appropriate government policy at this time to make the students always active with online education services. The aim is to break the chain of massive spread of the corona virus in the education areas. One solution for online learning at home is using Google classroom as an interactive learning media. It makes the teachers and students easy to do the teaching and learning process through the use of information and communication technology. Google classroom is currently so effective and efficient in space and time, that the teachers can provide the students with online-based teaching materials, ether in texts, images, audios, or videos. Such teaching materials enable the students to repeat the teaching materials distributed by the teacher continuously. Keywords: Corona Virus Diseas 19, Google Classrom, E-Learning, Teacher